Consumers’ Protection Under Murabahah Sale Contract (Journal of Social Sciences Review, 2023)
Murabahah is one of the contracts of sale of goods by a person to another under an agreement whereby the seller obliges himself to disclose to the buyer the cost of goods sold to the buyer, whether that is on a cash basis or deferred payment. The seller has to disclose to the buyer the margin of profit included in the sale price of goods agreed to be sold. It is a cost-plus markup sale, which is the ideal sale contract under Islamic Law. The basic theme of this research paper is to highlight the significance of the contract of Murabahah as a simple contract for the protection of consumers and not as a model of financing, which is prevalent in today’s Islamic banks. It aims to highlight its role in different types of sale contracts and its application to the sale of some major commodities. Both aspects of Murabahah, i.e., Murabahah as a simple sale contract for the protection of consumers and Murabahah financing, are discussed. The paper aims to explain how a simple Murabahah Contract protects the interest of consumers better than any other sale contract.
Keywords: Murabahah; Musawamah; Mark-up; Cost; Islamic Banking; Contract; Financing